Multiparametric image analysis reveals role of Caveolin1 in endosomal progression rather than internalization of EGFR - Schmidt-Glenewinkel, Hannah; Beaudouin, Joël; Legewie, Stefan; Eils, Roland (FEBS letters, 2012)
Endosomes constitute a central layer in the regulation of growth factor signaling. We applied flow cytometry, confocal microscopy and automated image quantification to define the role of Caveolin1 (Cav1) in epidermal growth factor (EGF) receptor (i) internalization and (ii) endosomal trafficking. Antisense-downregulation of Cav1 did not affect internalization of EGF:EGFR-complexes from the plasma membrane. Instead, Cav1-knockdown had a profound effect on endosomal trafficking and caused a shift in EGF vesicle distribution towards Rab7-negative compartments at late timepoints. Moreover, image quantification with single-endosome resolution revealed that EGF:Cav1-complexes undergo a maturation pattern reminiscent of late endosomes. Our data suggest a model in which Caveolin1 acts upon EGF endosomes internalized via the Clathrin-pathway and functions at the transition from early to late endosomes.